Recipient of 7 Deans List Awards, Nurul Nadiah receives 2 Excellence Awards - Nur Sa’adatul Afzan, Jusoh (2019)
Nurul Nadiah Abdul Halim, a graduate of Bachelor of Civil Engineering from the Faculty of Civil Engineering and Natural Resources, really made her parents proud when she obtained the Dean's Award for seven consecutive semesters.